Desenvolvimento e avaliação de uma lista de verificação para o ensino da assistência de enfermagem ao trabalho de parto, parto e nascimento - Nascimento, Izabela Cristina Fernandes do (2023)
The objective was to develop and evaluate a checklist for teaching nursing care during labor, delivery and birth. A methodological study based on the Checklist Development Checklist (CDC) method, consisting of 12 steps proposed by Stufflebeam (2000), was carried out in four topics: Topic 1- Initial checklist, Topic 2- Review process, Topic 3- Evaluation of the list by specialists in obstetrics and target audience and Topic 4- Completion of the list, with topic 1 covering steps 1 to 5, topic 2 steps 6 to 8, topic 3 encompassing step 9 and topic 4 referring to steps 10 to 12 of the CDC method. Data analysis took place by measuring the proportion of agreement between the specialists and the target audience, considering a Concordance Index (CI) greater than 80%. The research was approved by the Research Ethics Committee of the Federal University of Ceará, opinion No. 5,642,130. In step 1, the objectives of the checklist were defined and the study of the relevant literature on the content related to the theme of assistance in labor, delivery and birth was carried out. In step 2, the main aspects and their respective actions (checkpoints) related to teaching the practice of nursing care during labor, delivery and birth were listed. In step 3, the aspects listed in the previous step were placed in categories and then their respective actions (checkpoints) were placed in sequence following the logical order for the execution of a qualified assistance to childbirth. In step 4, the categories present in the checklist were justified regarding their relevance in carrying out normal risk vaginal delivery. In step 5, it was analyzed whether the actions should be carried out in the order established in the checklist. In step 6, a review version of the checklist was created for further critical review by an expert group. In step 7, the experts' suggestions were analyzed with adequacy of the checklist content, if necessary. In step 8, after adapting the content according to the experts' suggestions, the checklist was formatted based on the established categories. In step 9, the content and appearance were evaluated. The content evaluation was carried out by 32 specialists, 29 (90,63%) female aged between 28 and 64 years (44,40±10.79), 23 (71,87%) masters, 19 (59,37 %) doctors, 22 (68,75%) from the Northeast and 24 (75,00%) working in care and teaching. The CI was 97,46%. Experts suggested changes, such as: including active listening, mentioning hands on and hands off techniques, inserting the description of the Jacob Dublin maneuver, including inspection of the paraurethral region and digital rectal examination. The appearance assessment was carried out by the target audience consisting of 30 undergraduate nursing students from the Federal University of Ceará (UFC) who had already gone through the learning process of nursing care during labor, delivery and birth. 24 (80,00%) were female aged between 21 and 29 years (24,10±2.3). The CI was 99,17%. The target audience suggested adding how the Jacob-Dublin maneuver is performed. At the end of this stage, a pilot test was carried out with a group composed of a professor who teaches Obstetric Nursing and 18 students who are in the process of learning about nursing care during labor, delivery and birth at a public university from the municipality of Aracaju in the State of Sergipe. The list was made available during laboratory practices and in a real setting (delivery room), with a CI of 98,96% after laboratory practice, where students stated that the list promoted motivation and facilitated teaching and learning, stimulating the association between theory and practice and a CI of 100,00% after practice in a real scenario, where students reported that the list consolidated knowledge, helped to establish connections between theory and practice and in the preparation and performance of procedures. It is noteworthy that the use of the CDC method enabled the development of an innovative checklist for the teaching-learning of nursing care during labor, delivery and birth, which can generate important impacts on the quality of student teaching and care. provided when used as an educational tool. In view of the percentages of agreement index between specialists >97%, it is concluded that the checklist for teaching nursing care during labor, delivery and birth is a reliable and valid instrument for use in undergraduate Nursing.